Implementasi bahan ajar keterampilan membaca kritis bermuatan pesan moral dalam Cerpen Helvy Tiana Rosa - Sariyah Astuti; Dian Puspita (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to explore the implementation of Teaching Materials for Critical Reading Skills with Moral Messages, based on the short story "Helvy Tiada Rosa," for grade XI students at SMA 1 Pringsewu. The research method used Borg and Gall's R&D cycle approach, including steps ranging from data collection, product design, design validation, product trial, to product revision. The research instruments consisted of non-tests and tests, with validation of teaching materials by material experts. Data analysis was carried out descriptively. The results showed that the development of teaching materials was included in the "good" category, with the validation of the material aspects as a whole also categorized as "good." The effectiveness of the development of teaching materials is evidenced by the increase in students' knowledge, understanding, and skills, such as finding factual information, distinguishing opinions and facts, and assessing the suitability between the title and content of the reading. The skills of understanding moral messages, distinguishing reality from fantasy, and finding themes in literary works are also classified as very good.